2007
DOI: 10.1007/s10344-007-0134-y
|View full text |Cite
|
Sign up to set email alerts
|

Bullet-derived lead in tissues of the wild boar (Sus scrofa) and red deer (Cervus elaphus)

Abstract: Bullet-derived lead in game food products is an important source of human contamination. Careless removal of tissues from around the bullet pathway in the animal body results in elevated lead doses being ingested by humans. To assess bullet-derived lead contamination of soft game tissues, muscle tissue samples were collected from ten wild boars and ten red deer immediately after they had been shot. The samples were collected from around the entry and exit wounds, from around the bullet pathway at different sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 16 publications
5
34
0
1
Order By: Relevance
“…Against this background, these four samples were therefore excluded from the regression analysis while assessing the use of trace element concentrations in antlers as an index of concentration in muscle tissue. It has been shown that red deer muscle can be contaminated with Pb in the 30-cm neighboring area of the bullet pathway (Dobrowolska and Melosik 2008). In human, a diet including venison with high Pb concentration can result up to 2.5 times higher Pb exposure to the consumer, when we compare it to the exposure of human living on normal diet (EFSA 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Against this background, these four samples were therefore excluded from the regression analysis while assessing the use of trace element concentrations in antlers as an index of concentration in muscle tissue. It has been shown that red deer muscle can be contaminated with Pb in the 30-cm neighboring area of the bullet pathway (Dobrowolska and Melosik 2008). In human, a diet including venison with high Pb concentration can result up to 2.5 times higher Pb exposure to the consumer, when we compare it to the exposure of human living on normal diet (EFSA 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Lead fragments in gut piles from these and other game animals present risks to scavengers (Krone 2011). The ingestion of lead fragments from rifle-killed meat by humans is the latest component of this growing awareness of serious lead exposure (Dobrowolska and Melosik 2008;Kosnett 2009;Iqbal et al 2009;Knott et al 2010;Pain et al 2010), a risk that can be prevented by use of lead-free rifle ammunition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have linked elevated blood lead concentrations of subsistence hunters in northern Canada, Alaska, Greenland, and elsewhere to consumption of shotgun-killed birds [18-25; see 26,27]. The hypothesis that rifle bullet fragments are an additional source of human lead exposure is suggested by radiographic studies of deer killed with standard lead-based bullets, which show hundreds of small metal fragments widely dispersed around wound channels [28][29][30]. The possibility of inadvertent lead contamination in prepared meat consumed by hunters and their families is noteworthy, considering the millions of people who hunt big game in the U.S. [31] and the thousands of deer annually donated to food pantries for the poor [32,33].…”
Section: Introductionmentioning
confidence: 99%